Increased cerebral glucose utilization and decreased glucose transporter Glut1 during chronic hyperglycemia in rat brain - Duelli, Roman; Maurer, Martin H.; Staudt, Richard Erhard; Heiland, Sabine; Dümbgen, Lutz; Kuschinsky, Wolfgang (Brain research, 2000)
Whereas acute hyperglycemia has been shown to result in an unchanged local cerebral glucose utilization (LCGU) the changes of LCGU during chronic hyperglycemia are a matter of dispute. The present study had three aims: (1) To compare the effects of acute and chronic hyperglycemia on LCGU and to investigate in vivo the lactate level as a potential indicator of glycolytic flux. (2) To investigate local changes in brain Glut1 and/or Glut3 glucose transporter densities during chronic hyperglycemia. (3) To analyze the relationship between LCGU and local Glut densities during chronic hyperglycemia. To induce chronic hyperglycemia in rats steptozotocin was given i.p. and experiments were performed 3 weeks later. LCGU was measured by the 2−[14C]deoxyglucose method and intraparenchymal lactate concentration by MR-spectroscopy. Local densities of the glucose transport proteins were determined by immunoautoradiographic methods. During chronic hyperglycemia weighted average of LCGU increased by 13.9% whereas it remained unchanged during acute hyperglycemia. The cerebral lactate/choline ratio was increased by 143% during chronic hyperglycemia. The average density of glucose transporters Glut1 decreased by 7.5%. Local densities of Glut1 were decreased in 12 of 28 brain structures. Glut3 remained unchanged. Positive correlations were found between LCGU and local Glut densities during control conditions and during chronic hyperglycemia. It was concluded that (1) Chronic, but not acute hyperglycemia is followed by an increased LCGU. (2) The capacity to transport glucose is decreased during chronic hyperglycemia. (3) Increased LCGU and decreased densities of Glut1 are matched on a local level.